2009
DOI: 10.1111/j.1744-7909.2009.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Quantitative Trait Loci for Yield and Drought Tolerance Traits in Soybean Using a Recombinant Inbred Line Population

Abstract: To investigate the genetic basis of drought tolerance in soybean (Glycine max L. Merr.) a recombinant inbred population with 184 F(2:7:11) lines developed from a cross between Kefeng1 (drought tolerant) and Nannong1138-2 (drought sensitive) were tested under water-stressed and well-watered conditions in field and greenhouse trials. Traits measured included leaf wilting coefficient, excised leaf water loss and relative water content as indicators of plant water status and seed yield. A total of 40 quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Physiological mechanisms related to delayed wilting have now been identified in multiple soybean genotypes (Sloane et al 1990;Carter et al 1999;Fletcher et al 2007;King et al 2009;Ries et al 2012). Genetic studies of delayed wilting have identified QTLs, evaluated heritability, and reported relationships with other agronomic traits (Charlson et al 2009;Du et al 2009;Abdel-Haleem et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Physiological mechanisms related to delayed wilting have now been identified in multiple soybean genotypes (Sloane et al 1990;Carter et al 1999;Fletcher et al 2007;King et al 2009;Ries et al 2012). Genetic studies of delayed wilting have identified QTLs, evaluated heritability, and reported relationships with other agronomic traits (Charlson et al 2009;Du et al 2009;Abdel-Haleem et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the recombinant inbred line (RIL) population is immortal and can be used in different regions and times because it consists of homogenous individuals. The RIL population has been widely used for QTL mapping in crops (Balint-Kurti et al, 2008;Du et al, 2009;Blair et al, 2010;Zhou et al, 2011), but it has rarely been used for QTL mapping for traits associated with plant architecture in maize (Tang et al, 2007;Liu et al, 2010). Additionally, the same type of segregating population derived from different parental lines likely provide different QTL identification results, including different location, number, and genetic effects.…”
Section: Introductionmentioning
confidence: 99%
“…In case of abiotic stresses such as drought, cold, and heat, the main drivers of climate change very limited molecular marker analyses are available; however, efforts are underway to identify QTL underlying tolerances to these stresses. QTL for drought tolerance have been identified in soybean and chickpea (Millan et al 2006;Du et al 2009;Ur Rehman 2009). In case of soybean, Du et al (2009) detected 40 QTL in total, 17 for leaf water status traits under drought stress and 23 QTL for seed yield under wellwatered and drought-stressed conditions.…”
Section: Gene Discovery and Qtls For Tolerance To Stressesmentioning
confidence: 99%
“…QTL for drought tolerance have been identified in soybean and chickpea (Millan et al 2006;Du et al 2009;Ur Rehman 2009). In case of soybean, Du et al (2009) detected 40 QTL in total, 17 for leaf water status traits under drought stress and 23 QTL for seed yield under wellwatered and drought-stressed conditions. Two seed yield QTL were detected under both wellwatered and drought-stressed conditions in the field.…”
Section: Gene Discovery and Qtls For Tolerance To Stressesmentioning
confidence: 99%